A prospective study of injuries in basketball: a total profile and comparison by gender and standard of competition - McKay, G. D.; Goldie, P. A.; Payne, W. R.; Oakes, B. W.; Watson, L. F. (Journal of Science and Medicine in Sport, 2001)
The study aimed to determine prospectively a basketball injury profile, including severity of injury, and to compare the injury profile by gender and standard of competition. Trained observers viewed basketball games, noting the occurrence of injuries, and confirmed injuries by questioning all players on site after the game. Injured players completed a questionnaire and the progress of their injury was monitored by telephone interview. A total of 10,393 basketball participations were observed. An overall injury rate was documented of 18.3 per 1,000 participations (24.7 per 1,000 playing hours), and was comparable by gender and standard of competition. Serious injuries (missing one or more weeks of play) occurred at a rate of 2.89/1,000 participations; with the ankle joint the most common serious injury (1.25/1,000 participations), followed by the calf/anterior leg (0.48/1,000 participations) and knee joint (0.29/1,000 participations). The severity of the injury was significantly associated with the body region injured, with more serious injuries incurred to the lower limb than other body regions (p <.05). The severity of the injury incurred was not related to the standard of competition, gender, age, height, number of games played per week, amount of training undertaken, type of injury, or the mechanism of injury (p> .05).